In Vitro Shear Bond Strength of Orthodontic Brackets after Enamel Conditioning with Acid Etching and Hydroabrasion - Tepedino, Michele (Dent J (Basel), 2020)
The purpose of this study was to evaluate the shear bond strength and adhesive remnant index ARI) of orthodontic brackets following enamel conditioning with acid etching, hydroabrasion, and with both procedures. Thirty extracted human premolars were divided into three groups and received either acid etching, hydroabrasion or both procedures. Orthodontic brackets were bonded with composite resin. Shear bond strength was tested with a tensile machine, then the teeth were observed under a stereomicroscope to evaluate ARI scores. The enamel morphology after each conditioning method was evaluated with scanning electron microscope imaging. A one-way ANOVA and a Kruskal−Wallis H test were used to compare the bond strength and the ARI scores among the three groups. Hydroabrasion alone produced shear bond strength values below clinical acceptability, while the combination of acid etching and hydroabrasion produced the highest values. The ARI scores in the hydroabrasion group were significantly different from the other groups. Hydroabrasion followed by acid etching was effective in increasing the shear bond strength of orthodontic brackets. Further in vivo studies are needed to confirm the cost and benefits of this technique.